Composite particle, positive electrode, all-solid-state battery, and method of producing composite particle
A phosphorus compound coating with a specific composition ratio addresses the issue of resistance increase in sulfide-based all-solid-state batteries by enhancing Li ion conductivity and maintaining low resistance over time.
Patent Information
- Application Number
- JP2024176338
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2042-02-22
AI Technical Summary
Existing coatings for positive electrode active material particles in sulfide-based all-solid-state batteries reduce initial resistance but fail to maintain low resistance after durability tests, leading to a high increase in resistance over time.
A coating film containing a phosphorus compound with a specific composition ratio (C Li /C P ≤2.5) is applied to the positive electrode active material particles, formed using a phosphoric acid compound with a high mass fraction of diphosphorus pentoxide, to enhance Li ion conductivity and reduce initial resistance.
The coating film significantly reduces initial resistance and maintains a low resistance increase rate during durability tests, improving the battery's performance.
Smart Images

Figure 2024177508000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite particle, a positive electrode, an all-solid-state battery, and a method for producing the composite particle. [Background technology]
[0002] Japanese Patent Application Laid-Open No. 2012-099323 (Patent Document 1) discloses a coating layer containing Li3PO4. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-099323 A Summary of the Invention [Problem to be solved by the invention]
[0004] It has been proposed to form a coating film on the surface of positive electrode active material particles. For example, in sulfide-based all-solid-state batteries, the coating film is expected to reduce the initial resistance by preventing direct contact between the sulfide solid electrolyte and the positive electrode active material particles. However, there is room for improvement in the rate of increase in resistance after durability testing.
[0005] An object of the present disclosure is to reduce the initial resistance and the rate of increase in resistance. [Means for solving the problem]
[0006] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0007] 1. The composite particle includes a positive electrode active material particle and a coating film. The coating film covers at least a part of the surface of the positive electrode active material particle. The coating film includes a phosphorus compound. The composite particles satisfy the relationship of the following formula (1). CLi / C P <=2.5 (1) In the above formula (1), C Li indicates the elemental lithium concentration determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy. P indicates the elemental phosphorus concentration determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy.
[0008] Conventionally, coating films containing niobium compounds (LiNbO3) are well known. Coating films containing niobium compounds can reduce the initial resistance of batteries. However, they tend to have a high rate of resistance increase after durability tests.
[0009] According to the new findings of the present disclosure, a coating film containing a phosphorus compound tends to have a low resistance increase rate after a durability test, whereas a conventional film material (Li3PO4) tends to have a high initial resistance.
[0010] The coating film is required to exhibit Li-ion conductivity. It is believed that the higher the Li-ion conductivity, the lower the initial resistance. X-ray photoelectron spectroscopy (XPS) can be used to identify the composition of the particle surface (i.e., the composition of the coating film). In the case of conventional film materials (Li3PO4), the composition ratio (C Li / C P ) is considered to be 3 or more. In general, the composition ratio (C Li / C P ) is expected to increase (become Li-rich), improving the Li-ion conductivity and decreasing the initial resistance.
[0011] However, according to the new findings of the present disclosure, the composition ratio of the particle surface (C Li / C P ) being 2.5 or less, the initial resistance can be significantly reduced.
[0012] 2. The composite particles may have a coverage of, for example, 83% or more, as measured by X-ray photoelectron spectroscopy.
[0013] The details of the mechanism by which the initial resistance is reduced by satisfying the above formula (1) are unclear. According to the new findings of the present disclosure, when the above formula (1) is satisfied, the coverage tends to be high. Li / C P ) may affect the coverage and, as a result, reduce the initial resistance.
[0014] 3. The composite particles may contain 6.1 to 6.5% phosphorus by mass fraction.
[0015] 4. The positive electrode includes composite particles and a sulfide solid electrolyte. The composite particles include positive electrode active material particles and a coating film. The coating film covers at least a part of the surface of the positive electrode active material particles. The composite particles satisfy the relationship of the above formula (1).
[0016] 5. The composite particles may have a coverage of, for example, 83% or more, as measured by X-ray photoelectron spectroscopy.
[0017] 6. The composite particles may contain, for example, 6.1 to 6.5% phosphorus by mass fraction.
[0018] 7. An all-solid-state battery comprises the above positive electrode.
[0019] 8. A method for producing composite particles includes the following (a) and (b): (a) A mixture is prepared by mixing a coating liquid with positive electrode active material particles. (b) drying the mixture to produce composite particles. The coating liquid contains a phosphoric acid compound and a solvent. The phosphoric acid compound contains diphosphorus pentoxide in a mass fraction of 72% or more.
[0020] A coating film can be formed by drying the coating liquid attached to the surface of the positive electrode active material particles. The coating liquid contains a phosphoric acid compound. The phosphoric acid compound may be diphosphorus pentoxide (P2O5). P2O5 is also written as "phosphoric anhydride". The phosphoric acid compound may be a derivative of P2O5. The derivative of P2O5 can be produced by the reaction (hydrolysis) of P2O5 with water. According to the new findings of the present disclosure, when the mass fraction of P2O5 is 72% or more in a mixture of P2O5 and water, the composition ratio (C Li / C P ) is expected to be reduced.
[0021] The concentration (mass fraction) of P2O5 can be measured by a known method such as absorbance measurement.
[0022] 9. The phosphate compound may contain, for example, 72% or more by mass of diphosphorus pentoxide, with the remainder being water.
[0023] 10. The phosphate compound may include, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid.
[0024] Metaphosphoric acid (HPO3) n 〕 may contain 89% by mass of P2O5 and the remainder water (H2O). Polyphosphoric acid may contain, for example, 72 to 76% by mass of P2O5 and the remainder H2O. Note that since polyphosphoric acid is a mixture of various phosphoric acid compounds, it is difficult to express polyphosphoric acid by a specific chemical formula.
[0025] 11. The coating liquid may satisfy, for example, the relationship of the following formula (2). 0≦n Li / n P <1.1 (2) In the above formula (2), n Li indicates the molar concentration of lithium in the coating solution. P indicates the molar concentration of phosphorus in the coating solution.
[0026] "n Li / n P " indicates the molar ratio (substance amount ratio) of Li to P in the coating liquid. When the molar ratio is less than 1.1, composite particles that satisfy the above formula (1) tend to be formed. Note that the composition ratio (C Li / C P ) is the molar ratio (n Li / n P ) tends to be larger than the composition ratio (C Li / C P ) may increase.
[0027] 12. (b) above may include forming composite particles, for example by spray drying.
[0028] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing the all-solid-state battery in this embodiment. [Diagram 3] FIG. 3 is a schematic flow chart of the method for producing composite particles in this embodiment. [Figure 4] FIG. 4 is a graph showing the relationship between the composition ratio (CLi / CP) of the particle surface and the initial resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] <Definitions of terms, etc.> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0031] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0032] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0033] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.
[0034] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0035] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0036] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. In order to facilitate understanding of the disclosed technology, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.
[0037] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.
[0038] "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.
[0039] <XPS Measurement> (composition ratio of particle surface) C in the above formula (1) Li / CP can be measured by the following procedure. An XPS instrument is prepared. For example, an XPS instrument manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS instrument. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The peak area (integral value) of the Li1s spectrum is used as the elemental concentration of Li (C Li ) The peak area of the P2p spectrum is converted to the elemental concentration of P (C P ) is converted to C Li C P By dividing by Li / C P ) is obtained.
[0040] (Coverage rate) The coverage is also measured by XPS. By analyzing the above measurement data, the ratio of each element (element concentration) can be obtained from the peak areas of C1s, O1s, P2p, and M2p3. The coverage rate is calculated by the following formula (3). θ=P / (P+M)×100 (3) In the above formula (3), θ represents the coverage (%), and P and M represent the ratio of each element.
[0041] Note that "M2p3" and M in the above formula (3) are constituent elements of the positive electrode active material particles and represent an element other than Li and oxygen (O). That is, the positive electrode active material particles may be represented by the following formula (4). LiMO2(4) M may be composed of one element or multiple elements. M may be, for example, at least one element selected from the group consisting of Ni, Co, Mn, and Al. When M contains multiple elements, the total composition ratio of each element may be 1.
[0042] For example, the positive electrode active material particles are "LiNi1 / 3 Co 1 / 3 Mn 1 / 3 O2”, the above formula (3) can be transformed into the following formula (3′): θ=P / (P+Ni+Co+Mn)×100 (3') In the above formula (3'), Ni represents the element ratio of nickel determined from the peak area of Ni2p3, Co represents the element ratio of cobalt determined from the peak area of Co2p3, and Mn represents the element ratio of manganese determined from the peak area of Mn2p3.
[0043] <Film thickness measurement> The film thickness (thickness of the coating film) can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section is processed on the sample by an ion milling device. For example, an ion milling device "Product name Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by an SEM (Scanning Electron Microscope). For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The film thickness is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the film thicknesses at a total of 200 points is regarded as the film thickness.
[0044] 《ICP measurement》 (P adhesion amount) The mass fraction of P contained in the composite particles (also referred to as "P attachment amount" or "P content") can be measured by the following procedure. A mixed acid is prepared by mixing hydrochloric acid, nitric acid, and sulfuric acid. The mixing ratio is "hydrochloric acid / nitric acid / sulfuric acid = 2 / 3 / 1 (molar ratio)". A solution is prepared by dissolving the composite particles in the mixed acid. A sample solution is prepared by diluting 0.01 g of the solution to 100 mL with pure water. An aqueous solution of P (1000 ppm, 10000 ppm) is prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy) device is prepared. For example, an ICP-AES device manufactured by Shimadzu Corporation "Product name ICPE-9800" (or an equivalent product) may be used. The emission intensity of the standard solution is measured by the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The mass fraction of P contained in the composite particles is calculated from the emission intensity of the sample solution and the calibration curve.
[0045] (Mass concentration of Li, P, and Na in the coating solution) The mass concentrations of Li, P, and Na in the coating liquid are measured in the following procedure. 100 ml of sample liquid is prepared by diluting 0.01 g of the coating liquid with pure water. Aqueous solutions of Li, P, and Na (1000 ppm, 10000 ppm) are prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES device is prepared. The emission intensity of the standard solution is measured using the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The emission intensity of the sample liquid (diluted solution of the coating liquid) is measured using the ICP-AES device. The mass concentrations of Li, P, and Na in the coating liquid are determined from the emission intensity of the sample liquid and the calibration curve. The mass concentrations of Li and P are then converted to molar concentrations. The molar concentration of Li (n Li ) is the molar concentration of P (n P ) to obtain the molar ratio (n Li / n P ) is obtained.
[0046] <Composite particles> FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 5 may be called, for example, a "coated positive electrode active material". The composite particle 5 includes a positive electrode active material particle 1 and a coating film 2. The composite particle 5 may form, for example, an aggregate. That is, one composite particle 5 may include two or more positive electrode active material particles 1. The composite particle 5 may have, for example, a D50 of 1 to 50 μm, a D50 of 1 to 20 μm, or a D50 of 5 to 15 μm.
[0047] The coating film 2 is a shell of the composite particle 5. The coating film 2 covers at least a part of the surface of the positive electrode active material particle 1. The coating film 2 contains a phosphorus compound. The coating film 2 may contain, for example, P, Li, O, carbon (C), etc. By including the phosphorus compound in the coating film 2, a reduction in the rate of increase in resistance is expected.
[0048] The composite particle 5 may contain, for example, 6.1 to 6.5% P by mass fraction, or 6.1 to 6.2% P by mass fraction.
[0049] In the composite particle 5, the composition ratio of the particle surface (C Li / C P The composition ratio (C) is 2.5 or less (see formula (1) above). Li / C P By making the composition ratio (C) 2.5 or less, the initial resistance can be significantly reduced. Li / C P ) may be, for example, 2.44 or less, 2.05 or less, 1.73 or less, or 1.42 or less. Li / C P ) may be zero. Li / C P ) may be, for example, 0.1 or more, 0.5 or more, or 1.0 or more. Li / C P ) may be, for example, 1.42 to 2.44.
[0050] The coverage may be, for example, 83% or more. With a coverage of 83% or more, a reduction in initial resistance is expected. The coverage may be, for example, 85% or more, 88% or more, or 91% or more. The coverage may be, for example, 100%, 99% or less, or 95% or less. The coverage may be, for example, 83 to 91%.
[0051] The coating film 2 may have a thickness of, for example, 5 to 100 nm, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm.
[0052] The positive electrode active material particle 1 is a core of the composite particle 5. The positive electrode active material particle 1 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 1 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm. The primary particle may have a maximum Feret diameter of, for example, 0.1 to 3 μm.
[0053] The positive electrode active material particles 1 may contain any component. The positive electrode active material particles 1 may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2, Li(Ni 0.5 Co 0.2 Mn 0.3 )O2, Li(Ni 0.8 Co 0.1 Mn 0.1 ) O2, etc.
[0054] <All-solid-state battery> 2 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of an aluminum laminate film. The exterior body may house a power generating element 50. The power generating element 50 includes a positive electrode 10, a separator layer 30, and a negative electrode 20. That is, the all-solid-state battery 100 includes a positive electrode 10, a separator layer 30, and a negative electrode 20.
[0055] 《Positive electrode》 The positive electrode 10 is layered. The positive electrode 10 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, aluminum (Al) foil or the like. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0056] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 30. The positive electrode active material layer includes a positive electrode mixture. The positive electrode mixture includes composite particles and a sulfide solid electrolyte. That is, the positive electrode 10 includes composite particles and a sulfide solid electrolyte. Details of the composite particles are as described above.
[0057] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, with respect to 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte includes, for example, Li, P, and sulfur (S). The sulfide solid electrolyte may further include, for example, O, silicon (Si), or the like. The sulfide solid electrolyte may further include, for example, a halogen, or the like. The sulfide solid electrolyte may further include, for example, iodine (I), bromine (Br), or the like. The sulfide solid electrolyte may be, for example, glass ceramics or argyrodite. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0058] The positive electrode active material layer may further include, for example, a conductive material. The conductive material may form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake.
[0059] The positive electrode active material layer may further include, for example, a binder. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).
[0060] 《Negative electrode》 The negative electrode 20 is a counter electrode of the positive electrode 10. The negative electrode 20 is layered. The negative electrode 20 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode mixture to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, a copper (Cu) foil, a Ni foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0061] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 30. The negative electrode active material layer includes a negative electrode mixture. The negative electrode mixture includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode mixture may further include a conductive material and a binder. The sulfide solid electrolyte may be the same or different between the negative electrode mixture and the positive electrode mixture. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, silicon oxide [SiO x (0 <x<2)〕、およびLi4Ti5O 12 may contain at least one selected from the group consisting of:
[0062] <Separator layer> The separator layer 30 is interposed between the positive electrode 10 and the negative electrode 20. The separator layer 30 separates the positive electrode 10 from the negative electrode 20. The separator layer 30 includes a sulfide solid electrolyte. The separator layer 30 may further include a binder. The sulfide solid electrolyte may be the same or different between the separator layer 30 and the positive electrode composite. The sulfide solid electrolyte may be the same or different between the separator layer 30 and the negative electrode composite.
[0063] <Method of manufacturing composite particles> 3 is a schematic flow chart of the method for producing composite particles in this embodiment. Hereinafter, the "method for producing composite particles in this embodiment" may be abbreviated as "this production method". This production method includes "(a) preparation of a mixture" and "(b) production of composite particles". This production method may further include, for example, "(c) heat treatment" or the like.
[0064] (a) Preparation of the mixture The present manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles. The details of the positive electrode active material particles are as described above. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing positive electrode active material particles (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid into a powder. In the present manufacturing method, any mixing device, granulating device, etc. may be used.
[0065] The coating liquid contains a solute and a solvent. The solute contains a film material (raw material of the coating film). The coating liquid may further contain, for example, a suspended solid (insoluble component), a precipitate, and the like.
[0066] The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass, relative to 100 parts by mass of the solvent. The solvent may contain any component as long as the solute dissolves therein. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, etc.
[0067] The solute includes a phosphoric acid compound. The phosphoric acid compound may be P2O5 (phosphoric anhydride). The P2O5 may be in a powder form. The phosphoric acid compound may be formed by mixing P2O5 and water. However, P2O5 and water are mixed so that the mass fraction of P2O5 is 72% or more. That is, the phosphoric acid compound may contain P2O5 at a mass fraction of 72% or more, and the remainder water. By having P2O5 at 72% or more, the composition ratio (C Li / CP ) is expected to be reduced. The phosphate compound may contain, for example, 76% or more of P2O5 by mass fraction, may contain 84% or more of P2O5, or may contain 89% or more of P2O5 by mass fraction. The phosphate compound may contain, for example, 76 to 89% of P2O5 by mass fraction. By reducing the mass fraction of P2O5, the stability of the phosphate compound (pot life of the coating liquid) may also be improved.
[0068] The phosphoric acid compound may contain any component as long as the mass fraction of P2O5 is 72% or more. The phosphoric acid compound may contain at least one selected from the group consisting of orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, and polyphosphoric acid. The metaphosphoric acid may contain 89% by mass of P2O5. The metaphosphoric acid may be in a block form. The polyphosphoric acid may contain 76 to 84% by mass of P2O5. The polyphosphoric acid may be a highly viscous liquid. The orthophosphoric acid may contain 72% by mass of P2O5. The orthophosphoric acid may be a liquid.
[0069] The phosphate compound may contain at least one selected from the group consisting of, for example, metaphosphoric acid and polyphosphoric acid. This is because metaphosphoric acid and polyphosphoric acid can contain P2O5 at high concentrations. When the phosphate compound contains metaphosphoric acid and polyphosphoric acid, the composition ratio (C Li / C P ) is expected to be reduced.
[0070] The solute may further contain sodium (Na). When Na is dissolved in the coating liquid, the stability of the phosphate compound may be improved. The concentration (mass concentration) of Na in the coating liquid may be, for example, 0 to 1%. The concentration of Na may be, for example, 0.6% or less, or 0.5% or less. The concentration of Na may be, for example, 0.5 to 0.6%.
[0071] The solute may further include a lithium compound. The solute may include, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc. The molar ratio of Li to P (n Li / n P ) may be, for example, less than 1.1 (see formula (2) above). Li / n P ) is less than 1.1, so that the composition ratio (C Li / C P ) is expected to decrease. Li / n P ) may be, for example, 1.07 or less, 0.45 or less, or zero. Li / n P ) may be, for example, 0 to 0.45 or 0.45 to 1.07.
[0072] (b) Production of Composite Particles The present manufacturing method includes producing composite particles by drying the mixture. The coating liquid attached to the surface of the positive electrode active material particles is dried to produce a coating film. In the present manufacturing method, any drying method can be used.
[0073] For example, the composite particles may be formed by a spray-drying method. That is, the suspension is sprayed from a nozzle to form droplets. The droplets contain the positive electrode active material particles and the coating liquid. For example, the droplets are dried by hot air to form the composite particles. The use of the spray-drying method is expected to improve, for example, the coverage rate.
[0074] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.
[0075] For example, the composite particles may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of the mixture" and "(b) production of the composite particles" can be carried out simultaneously.
[0076] (c) Heat Treatment The present manufacturing method may include subjecting the composite particles to a heat treatment. The coating film may be fixed by the heat treatment. The heat treatment may also be called "baking". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air or in an inert atmosphere. EXAMPLES
[0077] <Manufacturing of all-solid-state batteries> Composite particles, positive electrodes, and all-solid-state batteries according to Nos. 1 to 10 were produced as follows. Hereinafter, for example, "composite particles according to No. 1" may be abbreviated as "No. 1."
[0078] No.1 A coating solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate (LiOH HO) was dissolved in the coating solution so that the conductivity was 0.45.
[0079] As the positive electrode active material particles, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3)O2 was prepared. 50 parts by mass of a powder of positive electrode active material particles was dispersed in 53.7 parts by mass of a coating liquid to prepare a suspension. A spray dryer manufactured by BUCHI (product name: Mini Spray Dryer B-290) was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. By the above procedure, the composition ratio (C Li / C P ), coverage, and P deposition were measured. The results are shown in Table 1 below.
[0080] The following materials were prepared: Sulfide solid electrolyte: 10LiI-15LiBr-75Li3PS4 Conductive material: VGCF Binder: SBR Dispersion medium: heptane Positive electrode collector: Aluminum foil
[0081] A positive electrode slurry was prepared by mixing the composite particles, the sulfide solid electrolyte, the conductive material, the binder, and the dispersion medium. The mixing ratio of the composite particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material was 3 parts by mass for 100 parts by mass of the composite particles. The amount of the binder was 3 parts by mass for 100 parts by mass of the composite particles. The positive electrode slurry was thoroughly stirred by an ultrasonic homogenizer. The positive electrode slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100 °C for 30 minutes by a hot plate. In this way, a positive electrode raw sheet was manufactured. A disk-shaped positive electrode was cut out from the positive electrode raw sheet. The area of the positive electrode was 1 cm2. 2 It was.
[0082] A negative electrode and a separator layer were prepared. The negative electrode active material particles were graphite. The same type of sulfide solid electrolyte was used between the positive electrode, the separator layer, and the negative electrode. The positive electrode, the separator layer, and the negative electrode were stacked in a cylindrical jig to form a laminate. The laminate was pressed to form a power generating element. A terminal was connected to the power generating element to form an all-solid-state battery.
[0083] No.2 A coating solution was prepared by dissolving 2.7 parts by mass of lithium metaphosphate (LiPO3, manufactured by Mitsuwa Chemical Co., Ltd.) in 50 parts by mass of ion-exchanged water. Except for this, composite particles, a positive electrode, and an all-solid-state battery were manufactured in the same manner as in No. 1.
[0084] No.3 A dry particle composite device manufactured by Hosokawa Micron Corporation (product name: Nobilta) was prepared. 50 parts by mass of positive electrode active material particles and 2.7 parts by mass of lithium orthophosphate (Li3PO4) were mixed in the dry particle composite device to form composite particles. After this, a positive electrode and an all-solid-state battery were manufactured in the same manner as in No. 1.
[0085] No.4 A coating solution was prepared by dissolving 31.6 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 500 parts by mass of ion-exchanged water. A lithium hydroxide aqueous solution was separately prepared by dissolving 34.5 parts by mass of lithium hydroxide monohydrate in 500 parts by mass of ion-exchanged water.
[0086] A tumbling fluidized coating device manufactured by Powrex Corporation (product name: MP-01) was prepared. A lithium hydroxide aqueous solution and a coating liquid were sprayed in sequence onto 1,000 parts by mass of positive electrode active material particles to form composite particles. The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. After this, a positive electrode and an all-solid-state battery were manufactured in the same manner as in No. 1.
[0087] No.5 A coating solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate was dissolved in the coating solution so that the σ was 3.00. After this, composite particles, a positive electrode, and an all-solid-state battery were produced in the same manner as in No. 1.
[0088] No.6 870.4 parts by mass of hydrogen peroxide solution (mass concentration 30%) were added to the container. Next, 987.4 parts by mass of ion-exchanged water and 44.2 parts by mass of niobic acid [Nb2O5·3H2O] were added to the container. Next, 87.9 parts by mass of ammonia water (mass concentration 28%) were added to the container. The contents of the container were thoroughly stirred to form a coating liquid. The coating liquid is believed to contain a Nb peroxo complex. From this point on, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1.
[0089] No.7 A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate was dissolved in the coating solution so that the ratio of the ionic liquid to the total surface area was 0.45. After this, the composite particles, the positive electrode, and the all-solid-state battery were fabricated in the same manner as in No. 1.
[0090] No.8 Composite particles, positive electrodes, and solid-state batteries were fabricated similarly to No. 7, except that no lithium hydroxide monohydrate was added to the coating solution.
[0091] No.9 By changing the amount of lithium hydroxide monohydrate added to the coating solution, the molar ratio (n Li / n PA composite particle, a positive electrode, and an all-solid-state battery were fabricated in the same manner as in No. 7, except that the composition of the positive electrode was changed.
[0092] No.10 A coating solution was prepared by dissolving 10 parts by mass of polyphosphoric acid (product name: Polyphosphoric acid-116T (manufactured by Nippon Chemical Industry Co., Ltd.)) in 166 parts by mass of ion-exchanged water. After this, composite particles, a positive electrode, and an all-solid-state battery were manufactured in the same manner as in No. 7.
[0093] <Evaluation> The initial resistance of the all-solid-state battery was measured. The results are shown in Table 1 below. The initial resistance in Table 1 below is a relative value. The initial resistance of No. 7 is defined as 1.
[0094] A durability test (high temperature storage test) of the all-solid-state battery was conducted under the following conditions.
[0095] Storage temperature (temperature chamber setting temperature): 60℃ Battery voltage at start of storage: 4.5V Storage period: 14 days
[0096] The resistance increase rate was calculated by dividing the resistance after the durability test by the initial resistance. The results are shown in the following Table 1. Note that the resistance increase rate of Nos. 1 to 5 was not measured because the initial resistance was very large.
[0097] [Table 1]
[0098] <Result> Figure 4 shows the composition ratio (C Li / C P ) and the initial resistance. Li / C P ) is 2.5 or less, the initial resistance is significantly reduced.
[0099] No. 6 showed low initial resistance. However, No. 6 had a high resistance increase rate. The coating film of No. 6 contains a niobium compound. Nos. 7 to 10 had low initial resistance and low resistance increase rates. The coating films of Nos. 7 to 10 contain a phosphorus compound.
[0100] <Additional Notes> This embodiment and this example also support the following coating liquid. 1. The coating liquid contains a phosphoric acid compound and a solvent. The phosphoric acid compound contains diphosphorus pentoxide in a mass fraction of 72% or more.
[0101] 2. The phosphate compound may contain 72% or more by mass of diphosphorus pentoxide, with the remainder being water.
[0102] 3. The phosphate compound may include at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid.
[0103] 4. The coating liquid may satisfy the relationship of the following formula (2). 0≦n Li / n P <1.1 (2) In the above formula (2), n Li indicates the molar concentration of lithium in the coating solution. P indicates the molar concentration of phosphorus in the coating solution.
[0104] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]
[0105] 1 positive electrode active material particle, 2 coating film, 5 composite particle, 10 positive electrode, 20 negative electrode, 30 separator layer, 50 power generating element, 100 all-solid-state battery.
Claims
1. Positive electrode active material particles; A coating film; Including, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains a phosphorus compound, The following formula (1): C Li / C P ≦2.5 (1) Fulfilling the relationship, In the above formula (1), C Li indicates the elemental concentration of lithium determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy, C P indicates the elemental concentration of phosphorus determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy, composite particles.
2. A coverage rate of 83% or more; The coverage is measured by X-ray photoelectron spectroscopy. The composite particle according to claim 1 .
3. Contains 6.1 to 6.5% phosphorus by mass fraction; The composite particle according to claim 1 or 2.
4. A composite particle; A sulfide solid electrolyte; Including, The composite particles include positive electrode active material particles and a coating film, the coating film covers at least a part of the surface of the positive electrode active material particle, The composite particles have the following formula (1): C Li / C P ≦2.5 (1) Fulfilling the relationship, In the above formula (1), C Liindicates the elemental concentration of lithium determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy, C P indicates the elemental concentration of phosphorus determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy, Positive electrode.
5. The composite particles have a coverage of 83% or more, The coverage is measured by X-ray photoelectron spectroscopy. The positive electrode according to claim 4 .
6. The composite particles contain 6.1 to 6.5% phosphorus by mass fraction. The positive electrode according to claim 4 or claim 5.
7. The positive electrode according to any one of claims 4 to 6, All-solid-state battery.
8. (a) preparing a mixture by mixing a coating liquid and positive electrode active material particles; and (b) drying the mixture to produce composite particles; Including, The coating liquid contains a phosphoric acid compound and a solvent, The phosphoric acid compound contains diphosphorus pentoxide in a mass fraction of 72% or more. A method for producing composite particles.
9. The phosphoric acid compound contains, by mass fraction, 72% or more of diphosphorus pentoxide and the remainder water. The method for producing composite particles according to claim 8 .
10. The phosphoric acid compound includes at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. The method for producing composite particles according to claim 8 or 9.
11. The coating liquid is The following formula (2): 0≦n Li / n P <1.1 (2) Fulfilling the relationship, In the above formula (2), n Li represents the molar concentration of lithium in the coating solution, n P represents the molar concentration of phosphorus in the coating liquid; The method for producing the composite particle according to any one of claims 8 to 10.
12. (b) includes forming the composite particles by a spray drying method; The method for producing the composite particle according to any one of claims 8 to 11.
Citation Information
Patent Citations
Positive electrode active material powder and manufacturing method thereof, and all-solid type lithium secondary battery
JP2018206669A
Electrode material and process for manufacturing electrode material
WO2014073652A1
Cathode active substance material, cathode active substance layer, all-solid battery, and method for producing cathode active substance material
JP2012099323A
